What drives the German TARGET balances? Evidence from a BVAR approach - Timo Bettendorf; Axel Jochem (Deutsche Bundesbank, 2021)
Applying a BVAR model, the present paper first identifies the possible drivers of Germany's TARGET claims. In this context, in terms of potential causes, a distinction is made between a rise in the global risk assessment, tensions within the euro area, and European monetary policy. It becomes evident that the TARGET flows between 2015 and 2017 can be ascribed in large part to monetary policy and to a minor extent to the risk assessment within the euro area. At the peak of the European debt crisis between 2010 and mid-2012, the TARGET flows were affected by uncertainty in the euro area as a dominant factor, although global factors also played a key role according to the model. The BVAR model we use opens up the possibility of studying the causes of current fluctuations in Germany's TARGET claims.
Keywords: C32; E52; F32; 330; target balances; risk; monetary policy; bayesian vector autoregression; sign restrictions